Bottlenose dolphins (Tursiops truncatus) do also cast neutrophil extracellular traps against the apicomplexan parasite Neospora caninum. Issue 3 (December 2017) - Villagra-Blanco, R.; Silva, L.M.R.; Aguilella-Segura, A.; Arcenillas-Hernández, I.; Martínez-Carrasco, C.; Seipp, A.; Gärtner, U.; Ruiz de Ybañez, R.; Taubert, A.; Hermosilla, C.
Abstract: Neutrophil extracellular traps (NETs) are web-like structures composed of nuclear DNA decorated with histones and cytoplasmic peptides which antiparasitic properties have not previously been investigated in cetaceans. Polymorphonuclear neutrophils (PMN) were isolated from healthy bottlenose dolphins ( Tursiops truncatus ), and stimulated with Neospora caninum tachyzoites and the NETs-agonist zymosan. In vitro interactions of PMN with the tachyzoites resulted in rapid extrusion of NETs. For the demonstration and quantification of cetacean NETs, extracellular DNA was stained by using either Sytox Orange ® or Pico Green ® . Scanning electron microscopy (SEM) and fluorescence analyses demonstrated PMN-derived release of NETs upon exposure to tachyzoites of N. caninum. Co-localization studies of N. caninum induced cetacean NETs proved the presence of DNA adorned with histones (H1, H2A/H2B, H3, H4), neutrophil elastase (NE), myeloperoxidase (MPO) and pentraxin (PTX) confirming the molecular properties of mammalian NETosis. Dolphin-derived N. caninum -NETosis were efficiently suppressed by DNase I and diphenyleneiodonium (DPI) treatments. Our results indicate that cetacean-derived NETs represent an ancient, conserved and relevant defense effector mechanism of the host innate immune system against N. caninum and probably other related neozoan parasites circulating in the marine environment. Graphical abstract: Image 1 Highlights: Cetacean derived-NETosis were quickly activated upon contact with N. caninum . Fluorescence analyses proved dolphin-NETs molecules upon exposure to N. caninum . N. caninum -triggered NETosis in dolphins was a NOX-dependent process. DNase I treatment suppressed NET formation signals in cetacean PMN.